Effect of grading type of aggregate on fracture parameters of concrete - Ince, Ragip; Cetin, Senem Yilmaz (Emerald Group Publishing Ltd, 2019)
Experimental studies have revealed that fracture parameters of concrete are mainly influenced by four material parameters: compressive strength, maximum aggregate size, water/cement ratio and aggregate type ( river or crushed). It has been noted that the fracture parameters of concrete can also be affected by other material parameters such as the type of cement, aggregate/sand ratio, porosity and curing conditions. Aggregates can be dense gap-graded or continuously graded in concrete technology. However, the effect of aggregate gradation ( continuously or gap-graded) on the fracture parameters of concrete has not been examined up until now. In this study, the notched and un-notched cubes produced by both gap and continuously graded batches were tested under splitting loading. The results are discussed based on the three most popular fracture approaches, namely the size effect law, the multi-fractal size effect law and the two-parameter fracture model. Although concretes made with an aggregate of either type of grading have similar mechanical properties such as compressive and tensile strength according to the literature, this study emphasises that the mixes with gap-graded aggregates indicate a more ductile behaviour than those with continuously graded aggregates for the same maximum aggregate size.
Keywords: aggregates; cracks & cracking; fracture & fracture mechanics